Toward a Nature-Based Economy - Chami, Ralph; Cosimano, Thomas; Fullenkamp, Connel; Nieburg, Dinah (Frontiers in Climate, 2022)
Humanity faces a dual threat to its existence: climate change and biodiversity loss. The two risks are linked through human activity and an economic system that promotes growth at the expense of nature. Creating a nature-based economy can mitigate the dual risks and bring sustained, shared prosperity. The paper shows how markets can be developed around the protection and regeneration of nature. Policies and actions needed to unleash the resources and innovation of markets to ensure that nature-based economic growth is shared and sustainable are specified. A nature-based economy ensures that conservation is a source of capital for development.